Study of circulating bearing current in a motor drive system - Muhammad Zulkarnain Hafiz Ismail (Nanyang Technological University, 2022)
This report aims to study the detrimental effect circulating bearing current has on a motor drive system, that is causing it to fault and eventually fail. The content of this report analyses the theoretical aspect this phenomenon, both on a healthy and faulty bearing. The design and fabrication of the experimental platform used to conduct vibration analysis of bearings were also discussed, prior to the investigation on the RUL of a bearing with varied health conditions by doing diagnostics and prognostics using machine learning.